2020
DOI: 10.38059/biodiversity.729081
|View full text |Cite
|
Sign up to set email alerts
|

Variation in biomass production of sunflower (Helianthus annuus) plants under the influence of Lemongrass (Cymbopogon erectus) extract

Abstract: Variation in biomass production of sunflower (Helianthus annuus) plants under the influence of Lemongrass (Cymbopogon erectus) extract Limon otu (Cymbopogon erectus) ekstresinin etkisi altında ayçiçeği (Helianthus annuus) bitkilerinin biyokütle üretiminde varyasyon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Growth rates were evaluated using the formulas presented below according to Paine et al (2012); Blackman (1919) 2017; Asad et al (2020). Simulated formulation was developed according to Poorter and Garnier (1998):…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth rates were evaluated using the formulas presented below according to Paine et al (2012); Blackman (1919) 2017; Asad et al (2020). Simulated formulation was developed according to Poorter and Garnier (1998):…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental approach for growth evaluation in plants has been focused on the elevated levels of carbon as a result of enhanced photosynthetic rate (Kanwal et al 2018;Muller et al 2011;Hummel et al 2010). There are several studies on biomass yield performance of trees and crops (Asad et al 2020). However, these studies explained the criterion of growth over the short-term period.…”
Section: Biomass and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported from various studies that alteration in seed germination may occur due to a number of factors i.e., changes in enzymatic activity, chromosomal sequencing and functioning of secondary metabolites (Khan et al, 2018;. Allelochemicals are usually responsible to induce phytotoxic effects and alter the ability of seed germination (Friedman et al, 1977;Baskin & Baskin, 2001;Asad et al, 2020). Chaves et al, (2001) revealed that the flavonoids present in Cistus ladanifer influenced the cotyledons size as well as limiting the germination % and slow down the cotyledon emergence.…”
Section: Effects On Germinationmentioning
confidence: 99%
“…Plants are the fundamental bodies in agriculture systems that accelerates world's economy, global food demand and socio-economic spectrum. Pakistan's economy also mainly depends upon agriculture however there are certain plants that can produce harmful effects in agricultural environment (Asad et al, 2020). Weeds are one of them.…”
Section: Introductionmentioning
confidence: 99%